KARAKTERISTIK TEKANAN LUAP DAN PENYEBABNYA PADA DAERAH LEPAS PANTAI SELAT MADURA - Yudha Risnandar Sinulingga; Agus Mochammad Ramdhan (Fakultas Ilmu dan Teknologi Kebumian (FITB), Institut Teknologi Bandung (ITB), 2017)
The East Java Basin is known as one of the prolific Tertiary hydrocarbon basin. This basin is also well known for its overpressure characteristic which occurs as a problem in drilling activity. Overpressure in East Java Basin generally occurs in Plio-Pleistocene interval which deposited in depression by rapid sedimentation rate. Wireline logs, pressure direct measurements, drilling mudweight and drilling events from four offshore exploration wells in Madura Strait are analysed to study overpressure characteristics and its mechanism. Eaton’s and Swarbrick’s Method are used to estimate the magnitude of pore pressure in research area. The location of research area within Kendeng Trough that physiographycally is a continuation of Kendeng-Randublatung Depression to the east might cause rapid sedimentation of thick sediment that would led to the generation of overpressure.